Exploring Five Methods for Estimating Net Community Production on the Siberian Continental Shelf and Slope of the Arctic Ocean - Alkire, M. B.; Polyakov, I.; Macdonald, R. W. (Frontiers in Marine Science, 2022)
The loss of sea ice and changes to vertical stratification in the Arctic Ocean are altering the availability of light and nutrients, with significant consequences for net community production (NCP) and carbon export. However, a general lack of quality data, particular during winter months, inhibits our ability to quantify such change. As a result, two parameters necessary for calculating annual NCP, integration depth (Zint) and pre-bloom nitrate concentration (Npre), are often either assigned or estimated from summer measurements. Vertical profiles of temperature, salinity, nitrate, and dissolved oxygen were collected during three cruises conducted between August and October of 2013, 2015, and 2018 in a data-sparse region of the Arctic Ocean along the Siberian continental slope. Estimates of NCP were calculated from these data using five different methods that either assigned constant values for Zint and/or Npre or estimated these parameters from summer observations. The five methods returned similar mean values of Zint (44-54 m), Npre (5.4-5.7 mmol m-3), and NCP (12-16 g C m-2) across the study region; however, there was considerable variability among stations/profiles. It was determined that the NCP calculations were particularly sensitive to the Npre. Despite this sensitivity, mean NCP estimates calculated along four transects re-occupied during the three cruises generally agreed across the five methods with two important exceptions. First, methods with pre-assigned Zint and/or Npre underestimated the NCP when the nitracline shoaled in the Laptev Sea and when high-nutrient shelf waters were advected northward from the East Siberian Sea shelf in 2015. In contrast, the methods that directly estimated both Zint and Npre did not suffer from this bias. These results suggest that assignment of Npre and/or Zint provides reasonable estimates of NCP, particularly averaged over larger spatial scales and/or longer time scales, but these approaches are not suitable for evaluating interannual variability in NCP, particularly in dynamic regions. Combining all methods across the three cruise years indicates NCP in the Laptev Sea and Lomonosov Ridge areas (10-11 g C m-2) was slightly lower than that north of Severnaya Zemlya (13 g C m-2) and in the East Siberian Sea (16 g C m-2).